Structural and Morphological Studies of V2O5/MWCNTs and ZrO2/MWCNTs Composites as Photocatalysts - Sajid Iqbal; Tanveer Hussain Bokhari; Shoomaila Latif; Muhammad Imran; Ayesha Javaid; Liviu Mitu (Journal of Chemistry)
The present study outlines the synthesis of transition metal oxide- (TMO-) multiwall carbon nanotubes- (MWCNTs-) based composites for photocatalytic application. MWCNTs were functionalized/purified by treating with H2SO4 and HNO3 to improve their dispersion in water. The TMOs (ZrO2, V2O5) were decorated on MWCNTs by the hydrothermal method to yield V2O5/MWCNTs and ZrO2/MWCNTs composites. Subsequently, these composites were characterized for their structural/morphological studies by Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), and scanning electron microscopy (SEM). Photocatalytic activities of TMO/MWCNTs composites were investigated by degradation phenomenon of methylene blue (MB) dye in aqueous solution. It was observed that the prepared composites best performed in the presence of H2O2 under ultraviolet irradiation. The maximum observed degradation efficiencies for ZrO2/MWCNTs and V2O5/MWCNTs were 49% and 96%, respectively.